An Experimental Study to Assess the Effectiveness of Progressive Muscle Relaxation Technique on Post-operative Pain Management in Patients Undergoing Abdominal Surgery in Gauhati Medical College and Hospital, Guwahati, Assam - Nabiya Ahmed, Rukiya (International Journal of Nursing Research, 2023)
Background: Effective pain management is essential in the post-operative period to ensure that patients do not experience unnecessary distress or suffering and to minimize potential complications. One of the most simple and easy learned techniques for relaxation is progressive muscle relaxation (PMR) technique. Aim: This study aims to assess the effectiveness of PMR technique on post-operative pain management in patients undergoing abdominal surgery in Gauhati Medical College and Hospital, Guwahati, Assam. Materials and Methods: A quasi-experimental, pretest-post-test control group design was selected for the study. Convenient sampling technique was used to select 40 patients in the experimental and control groups by simple randomization. Analysis and interpretation: Results: The findings of the study revealed that on pre-test assessment, it was observed that in day 1, majority of patients had moderate pain both in the experimental and control groups, that is, 90% and 85%, respectively. In day 2 also, majority of patients in both the experimental group and control group had moderate pain, that is, 75% and 65%, respectively. In day 3, majority of patients had mild pain in both the experimental group and control group, that is, 95% and 85%, respectively. It was found that there was no significant association between the selected variables and level of pain in patients undergoing abdominal surgery. The pre-test and post-test observation on the 1st and 2nd post-operative day by paired t-test was significant (P < 0.05) in the experimental group. On the 3rd post-operative day, t value was significant in both the experimental and control groups (P < 0.01). Conclusion: It can be concluded that PMR technique was effective in reducing level of post-operative pain on the 1st and 2nd post-operative days after abdominal surgery